Cytopathological and bacteriological studies on caseous lymphadenitis in cattle slaughtered at Bishoftu municipal abattoir, Ethiopia - Mesfin Mathewos; Haben Fesseha (Veterinary Medicine and Science, 2022)
Abstract Background Caseous lymphadenitis (CLA) is a chronic bacterial infectious disease that affects cattle, shoats, and other domestic and wild ruminants. Methods A purposive cross‐sectional study was conducted on 30 cattle with enlarged lymph nodes to investigate CLA using cytopathological and bacteriological techniques from cattle slaughtered at Bishoftu municipal abattoir. Results From a total of 30 cattle subjected to clinical and post‐mortem examinations, only one bull was found to be infected with a rare case of CLA in Bishoftu municipal abattoir, Ethiopia. Enlargement of the pre‐scapular lymph node was the only clinical finding during ante‐mortem inspection of the bull. The gross pathological lesion showed a pre‐scapular lymph node with a caseo‐necrotic dystrophic calcification that was accompanied by a rough texture and white to grayish hue. Histopathologically, the lymph node was characterized by central liquefactive necrosis that was surrounded by coagulative necrosis containing multiple foci of mineralization, infiltration of polymorphonuclear neutrophils and mononuclear immature fibrosis containing inflammatory cells and also with some sort of a thick layer of mature fibrosis that defines the magnitude of the lesion. Cytologically, multi‐lobulated (intact and degenerated) neutrophils, a few reactive lymphocytes, macrophages and some crenated histocytes have been recognized. The bacterial culture of the sample revealed small, white cream, dry, waxy colonies with a narrow area of β‐haemolysis. The isolate of the sample was a Gram‐positive cocci‐bacilli that was arranged in a Chinese pattern on Gram staining, and catalase and urease were positive in the biochemical analysis of this organism, which was able to ferment glucose and maltose but not trehalose and xylose. Conclusions The present investigation indicated that CLA was prevalent as sporadic cases among cattle slaughtered in Bishoftu municipal abattoir. Thus, effective preventive and control measures, such as good sanitation and hygiene, should be followed during meat inspection.